VEGETATION OF THE WESTERN COAST OF THE BAIDARATSKAYA BAY AT THE END OF THE LATE PLEISTOCENE - Andreev A.A.; Terekhov K.I.; Tarasov P.E.; Romanenko F.A.; Sulerzhitskii L.D. (My University, 1998)
The results of palynological analysis of a section of unconsolidated deposits in the 12-m-high coastal escarpment of the Baidaratskaya Bay (68°51′N, 66°54′E), the southeastern part of the Yugorskii Peninsula, are outlined. The section includes the lower member of sandy loam rich in ice, presumably accumulated in the late glacial time. The upper peat member was accumulated between 8 and 4 ka ago. The rough boundary between peat and oxbow-lake loams with cryoturbation marks suggests a hiatus in sedimentation between 10.9 and 8.2 ka ago. The age of deposits was determined by the radiocarbon method. The results of palynological analysis reveal several phases of vegetation development in the study area and specify their time limits. We believe that the Allerod warming period was more favorable than the Middle Holocene for the development of arboreal-fritucose vegetation in the region now occupied by typical tundras. This is likely a result of the sea level rise at the end of the late Pleistocene and in the first half of the Holocene up to altitudes somewhat exceeding the recent level, when the influence of the ocean upon climate and vegetation was enhanced.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен